Green Architecture As continuous phenomena - Rana Mazin Mahdi; Zainab Hussein R’aouf (Iraqi Journal of Architecture and Planning)
Architects today interest about "Green architecture as continuous phenomena" deals with problems today throw haring so many system treat this problems. So this research is attempt to study both conceptual and practical levels for green architecture to significant its style. So research problem represented by (there was no image about what considers make green architecture as continuous phenomena). So the research goal is (significant the considers which makes green architecture as continuous phenomena) the hypotheses of research is (Green architecture in its conceptual and practical level has some and vocabulary with confirm green architecture as continuous phenomena)